The underlying molecular mechanisms of Fyn in neonatal hypoxic-ischaemic encephalopathy - Zhou, Jiao; Lu, Xiang; Wang, Haichuan (Frontiers in Cellular Neuroscience, 2024)
Fyn is a cytoplasmic tyrosine kinase (TK) that is a nonreceptor and a member of the Src family of kinases (SFKs). It is involved in several transduction pathways in the central nervous system (CNS), such as oligodendrocyte development, myelination, axon guidance, and synaptic transmission. Owing to its wide range of activities in the molecular signalling pathways that underpin both neuropathologic and neurodevelopmental events, Fyn has remained of great interest for more than a century. Accumulating preclinical data have highlighted the potential role of Fyn in the pathophysiology of neonatal hypoxic-ischaemic encephalopathy (HIE). By mediating important signalling pathways, Fyn may control glutamate excitotoxicity, promote neuroinflammation and facilitate the death of neurons caused by oxidative stress. In this review, we address new evidence regarding the role of Fyn in the pathogenesis of this condition, with the aim of providing a reference for the development of new strategies to improve the prognosis of neonatal HIE. In addition, we also offer insights into additional Fyn-related molecular mechanisms involved in HIE pathology.